Retórica do luto: temas filosóficos e oratória em Sêneca - Sarah Nilza Araújo da Silva Zinato (2024)
The present work proposes the translation and comments on the Consolatio ad Marciam and on three Epistulae Morales by Seneca (63, 93 and 99), carrying out a study of the works. In this field, the focuses of the proposed study are three. Firstly, to consider Stoic philosophical themes and observe the conception of death and mourning, key points in our analysis in relation to the selected works, mainly from the author's perspective. Secondly, we aim to understand the structure of consolatio within the rhetorical-literary tradition and the stylistic traits of Seneca, as a personality of immeasurable literary and philosophical importance in the Roman perspective. Finally, to undertake an analysis of the structure of Seneca's consolation and the rhetorical strategies that provide the selected works their distinctive character, both due to their consolation status and due to Seneca's language and style, recognizing the characteristics that allow us to observe and outline the author's thought. In this sense, translation is fundamental, seeking to preserve the stylistic features of the original work.